Os impactos da Segunda Guerra Mundial e a regulação das relações de trabalho no Brasil - Alexandre Fortes (Nuevo mundo - Mundos Nuevos, 2014)
This article departs from the assumption that World War II was a global process with profoundly transforming impacts on economic, social and political relations even in areas removed from the main battle zones. Integrating elements from labor history and foreign relations history, we search to demonstrate how the exam of the war impact on Brazil brings new interpretations on the consolidation of the institutional engineering for state-controlled regulation of labor relations characteristic of the so-called “Vargas Age”. This approach allows us to understand the reinvention of the Brazilian state at that critical juncture, under the pressure of profound and accelerated transformations, both “top-down” and “bottom-up”, resulting in political-institutional innovations, with lasting effects. In one hand, there is the emergence of a new international order in which industrialization was established as a sine qua non condition for national sovereignty. On the other hand, the project of a “controlled” incorporation of the subaltern majorities to citizenship and political participation, in a context marked by the novel popularity of communism, also one in which the ideological defeat of “scientific racism” shook the foundations of post-abolition social hierarchies.